178 Use of silvopastures and woodlands to expand the grazing opportunity for small ruminants. (28th November 2020) - Karki, Uma
Abstract: Pasture-based small-ruminant farming is a popular enterprise in the Southeast, especially for small and limited-resource producers. Although woodlands occupy a majority of the land cover in the South and can be a promising resource for raising small ruminants, not much attention has been given on using such resources. A series of studies were conducted at the facilities of Tuskegee University with the overall objective of exploring the potential of using silvopastures and woodlands for raising small ruminants. Grazing studies were conducted from 2015 to 2019 using meat goats and hair sheep in silvopastures and woodland plots. Silvopastures were developed by thinning down the existing woodlands and planting suitable cool- and warm-season forages. Grazing facilities were installed in the study plots and animals were rotationally stocked each year during both cool- and warm-season grazing periods. In 2017, non-pine plants in woodlands were cut to three different heights (ground level and 0.9 m and 1.5 m from the ground level) or left uncut (control) to see the effects on understory vegetation biomass production and utilization by small ruminants. Data on vegetation biomass and quality, canopy height, animal performance and behavior, browsing height, and vegetation preference were collected and analyzed. Small ruminants were found to utilize all planted forages (silvopastures) well and most of the understory plants in woodlands. Vegetation biomass in woodlands increased in areas where non-pine plants were cut versus the control (36–106%; P < 0.0001). Mature animals maintained a desirable body condition score (≥2.6) and FAMACHA score (≤2.6) in woodlands. However, young, growing animals showed a poor live weight gain, especially during some portion of the study. Animals performed well when they were stocked in silvopastures. Both species showed a similar preference for most plant species available in woodlands. Results show a tremendous potential of using silvopastures and woodlands for expanding the grazing opportunity for small ruminants. However, the provision of some supplements would be necessary while stocking young animals in woodlands.